2001
DOI: 10.1074/jbc.m103879200
|View full text |Cite
|
Sign up to set email alerts
|

Pro-apoptotic Cleavage Products of Bcl-xL Form Cytochrome c-conducting Pores in Pure Lipid Membranes

Abstract: During apoptotic cell death, cells usually release apoptogenic proteins such as cytochrome c from the mitochondrial intermembrane space. If Bcl-2 family proteins induce such release by increasing outer mitochondrial membrane permeability, then the pro-apoptotic, but not anti-apoptotic activity of these proteins should correlate with their permeabilization of membranes to cytochrome c. Here, we tested this hypothesis using pro-survival fulllength Bcl-x L and pro-death Bcl-x L cleavage products (⌬N61Bcl-x L and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 72 publications
5
127
1
Order By: Relevance
“…Although these drugs are generally thought to inactivate anti-death Bcl-2 family proteins, it remains possible that they also activate latent pro-death functions of Bcl-2 and Bcl-xL. In this scenario, the drugs would have an effect similar to proteolytic cleavage of Bcl-2 and Bcl-xL, whereby Bcl-2 and Bcl-xL gain the ability to potently kill cells and to release cytochrome c from intracellular and isolated mitochondria and from pure lipid vesicles (Cheng et al, 1997;Clem et al, 1998;Basan˜ez et al, 2001). An important outcome of the work on various BH3-only proteins (including Bid, Bad, Hrk, Bim, Puma, Noxa and several others) is that we are now armed with the understanding that the binding capacities of Bcl-2 family proteins differ in healthy and dying cells (Suzuki et al, 2000;Wilson-Annan et al, 2003;Jeong et al, 2004).…”
Section: The Executioner Mitochondrionmentioning
confidence: 99%
“…Although these drugs are generally thought to inactivate anti-death Bcl-2 family proteins, it remains possible that they also activate latent pro-death functions of Bcl-2 and Bcl-xL. In this scenario, the drugs would have an effect similar to proteolytic cleavage of Bcl-2 and Bcl-xL, whereby Bcl-2 and Bcl-xL gain the ability to potently kill cells and to release cytochrome c from intracellular and isolated mitochondria and from pure lipid vesicles (Cheng et al, 1997;Clem et al, 1998;Basan˜ez et al, 2001). An important outcome of the work on various BH3-only proteins (including Bid, Bad, Hrk, Bim, Puma, Noxa and several others) is that we are now armed with the understanding that the binding capacities of Bcl-2 family proteins differ in healthy and dying cells (Suzuki et al, 2000;Wilson-Annan et al, 2003;Jeong et al, 2004).…”
Section: The Executioner Mitochondrionmentioning
confidence: 99%
“…5C). Like Bcl-xL lacking its C-terminal hydrophobic domain (Basañez et al 2001), ⌬CFis1 became active only when the pH was lowered from pH 7 to pH 5 (Fig. 5D, bottom).…”
Section: Yeast Fis1 Porates Lipid Vesicles Similar To Human Bcl-xlmentioning
confidence: 99%
“…Nevertheless, we investigated the possibility that yeast Fis1 may share some biophysical properties of Bcl-2/Bcl-xL. Bcl-xL forms pores in synthetic lipid membranes and induces channels on intracellular mitochondria that correlate with its effects on synaptic activity (Basañez et al 2001;Vander Heiden et al 2001;Jonas et al 2003Jonas et al , 2004. Similar to human Bcl-xL, we found that recombinant yeast Fis1 protein efficiently released >80% of 0.4 kDa and 10% of 4 kDa but not larger molecules in a dose-dependent manner from pure lipid vesicles (large unilammelar vesicles, LUV) (Fig.…”
Section: Yeast Fis1 Porates Lipid Vesicles Similar To Human Bcl-xlmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,46 ± 48 The resulting C-terminal cleavage product is a potent BAX-like pro-apoptotic factor. 3,49,50 Mutation of the caspase cleavage sites causes BCL-2 and BCL-x L to become more potently protective than wild type proteins, arguing that cleavage is an important intracellular event for regulating cell survival/ death. 2,3 Cleavage of BCL-2 may be important in chemotherapy-induced death of leukemia/lymphoma cells, 51,52 and in the death of hepatocytes in mice treated with an antibody to activate the Fas death receptor pathway.…”
Section: Homology Between Cellular and Viral Bcl-2 Familymentioning
confidence: 99%